Negosiasi Identitas Perempuan dalam Ruang Budaya Maskulin: Studi Etnografi Paguyuban Reog Putri Sardulo Nareswari, Ponorogo - Janah, Defi Asiatul; Suryandari, Nikmah (Jurnal Audiens, 2025)
Art is an important part of culture, serving as a medium for expressing the soul, experience, and identity of a community. Reog, a tradition traditionally performed by men and considered sacred, is deeply embedded in social norms, making it difficult to change. The emergence of women's groups such as Sardulo Nareswari has sparked resistance because it is considered a violation of tradition. This research, using qualitative ethnographic studies, allows researchers to conduct in-depth, participatory observations. The purpose of this study is to analyze how Sardulo Nareswari women negotiate identity within a masculine cultural space. The results of Sardulo Nareswari's research use negotiation strategies of compromising, accommodating, competing (maintaining identity), and collaborating, without using avoiding strategies (avoiding conflict). This strategy demonstrates social intelligence and flexibility in facing complex cultural challenges, strengthening their legitimacy and existence as female Reog artists in Ponorogo, while simultaneously preserving culture despite being in a cultural space dominated by masculinity. This research provides a new contribution to the study of gender communication studies by expanding Ting-Toomey's identity negotiation framework within a traditional cultural context.